PRINCIPLE OF APPLICATION OF ADMINISTRATIVE COERCION MEASURES BY THE MILITARY LAW ORDER SERVICE IN THE ARMED FORCES OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
It was found that the principles of applying administrative coercion measures represent indisputable requirements, rules for applying appropriate measures and are reflected in legal norms, the purpose of which is to reconcile the social necessity of applying such measures and the interests of the public in the inviolability of universal human values recognized by law. It was noted that these principles are not singled out in a separate list in the norms of current legislation, but they are only deduced from the content of those acts that regulate the work of the Law Enforcement Service. Three groups of principles of applying administrative coercion measures by the Military Law Enforcement Service in the Armed Forces of Ukraine are distinguished, in particular: general legal, sectoral and special. Thus, the general legal ones include the principles of legality, respect for the individual, his rights and freedoms, etc. In turn, the sectoral principles of administrative law, which include: centralized management and single leadership, interaction with the public, are aimed at: first, reflecting the influence of general principles of law and principles of administrative management on the regularities of the activities of the Law Enforcement Service; second, adapting the basic values laid down by the first two groups of principles to the scope of application of administrative coercive measures. It is argued that the following should be included in the group of specific principles: proportionality, i.e. the correspondence of coercive measures to the actions that the serviceman of the Law Enforcement Service intends to prevent, stop, or facilitate; expediency, which is manifested in the fact that the application of such measures, taking into account the external conditions of objective reality, is optimal for achieving a certain goal; individual responsibility of the serviceman for choosing and adhering to the procedure for implementing such a measure; limitedness, in particular, the legislation defines certain places and a range of subjects in relation to which certain measures of administrative coercion are prohibited under certain conditions; the absence of discrimination, personal preferences or dislike of a serviceman towards a person due to sexual, political, social, religious, racial, national or other affiliation should not influence the choice of applying a measure of administrative coercion.
Keywords: principles; principles of law; measures; administrative coercion; Military Law Enforcement Service